Synthetic applications of the cyclic iminocarbonate rearrangement: enantioselective syntheses of chloramphenicol and 4-epi-cytoxazone - Park, JN; Ko, SY; Koh, HY (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Chloramphenicol and 4-epi-cytoxazone have been enantioselectively synthesized using the asymmetric dihydroxylation and the cyclic iminocarbonate rearrangement as key steps. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: BETA-AMINO ACIDS; CYTOKINE MODULATOR; ASYMMETRIC AMINOHYDROXYLATION; CYTOXAZONE; DIHYDROXYLATION